Understanding Frames of the State-Sponsored Media Tweets During the 2019 Hong Kong Protests - Kim, Ji Young (Department of Communications, Universitas Islam Indonesia, 2022)
In this current study, Chinese government’s strategic communication efforts were explored in the context of the 2019 Hong Kong protests via state-sponsored media tweets. To understand how the government conveyed the protests and how it is engaged with other stakeholders, tweets were examined inductively in terms of frames and stakeholders. Recognizing the strategic nature of agenda building, message frames, stakeholders, and their characteristics and relationships around the issues were the key aspects of understanding the issue. Results show the multiple frames identified to understand how the protests were described, who the main actors were, and how their relationships were presented in the social media messages. The representation of the stakeholders or frames in the social media messages changed over a short period. The roles of state-sponsored tweets as strategic public diplomacy tools and information sources are discussed.